2004
DOI: 10.1029/2003ja010150
|View full text |Cite
|
Sign up to set email alerts
|

Modeling a space weather event from the Sun to the Earth: CME generation and interplanetary propagation

Abstract: [1] We present a three-dimensional (3-D) numerical ideal magnetohydrodynamics (MHD) model describing the time-dependent expulsion of a coronal mass ejection (CME) from the solar corona propagating to 1 astronomical unit (AU). The simulations are performed using the Block Adaptive Tree Solar-Wind Roe Upwind Scheme (BATS-R-US) code. We begin by developing a global steady-state model of the corona that possesses high-latitude coronal holes and a helmet streamer structure with a current sheet at the equator. The A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
325
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(343 citation statements)
references
References 38 publications
14
325
1
Order By: Relevance
“…Using 2-D and 3-D numerical simulations, it is possible to show that a CME initiated at the solar surface (for example using a twisted flux rope) evolves through its interaction with the solar wind into a typical ICME (Riley, Gosling, and Pizzo, 1997;Odstrčil and Pizzo, 1999;Manchester et al, 2004;Chané et al, 2006;Shen et al, 2007). This idea has now been confirmed by STEREO observations (see, for example, Savani et al, 2010).…”
Section: Introductionmentioning
confidence: 79%
“…Using 2-D and 3-D numerical simulations, it is possible to show that a CME initiated at the solar surface (for example using a twisted flux rope) evolves through its interaction with the solar wind into a typical ICME (Riley, Gosling, and Pizzo, 1997;Odstrčil and Pizzo, 1999;Manchester et al, 2004;Chané et al, 2006;Shen et al, 2007). This idea has now been confirmed by STEREO observations (see, for example, Savani et al, 2010).…”
Section: Introductionmentioning
confidence: 79%
“…2.4). However, values of a larger than ≈ √ b are expected to be unphysical (in particular they were not found in MHD simulations, e.g., Riley et al 2003;Manchester et al 2004), so we claim that Fig. 11 represents a sufficiently broad range of the parameter space which covers most of the observed MC configurations.…”
Section: Bendingmentioning
confidence: 87%
“…In some MHD simulations, the flux rope is strongly compressed in the propagation direction, such that it becomes relatively flat (e.g., Vandas et al 2002), and it can even develop a bending of the lateral sides towards the front direction as it moves away from the Sun (e.g., Riley et al 2003;Manchester et al 2004). Owens et al (2006) proposed a kinematic model of this evolution with an initial Lundquist solution passively deformed by a given velocity flow.…”
Section: Introductionmentioning
confidence: 99%
“…They have studied with the use of global MHD simulations in 3D (Manchester et al 2004;Lugaz & Roussev 2011;Shiota & Kataoka 2016). Liu et al (2013) reported the first detailed examination of the Sun-to-Earth propagation characteristics of three fast CMEs and an associated shock front using the combination of wideangle heliospheric imaging observations by STEREO, interplanetary Type II radio bursts, and in situ observations of solar wind parameters at multiple points.…”
Section: Introductionmentioning
confidence: 99%